PEMBUATAN APLIKASI PEMASUKKAN & PENGELUARAN BARANG LOGISTIK BERBASIS WEB DENGAN METODE FIFO (FISRT IN FIRST OUT) MENGGUNAKAN PHP & MYSQL PADA PT . NETCITI PERSADA - Juan Ripandi; Alif Nurcahyo; RATAMA, Fahrid Firdaus; RATAMA, Suhanda Saputra (Journal of Research and Publication Innovation, 2024)
The inventory application is a transaction processing system built to manage inventory. So far, many companies have used inventory applications in their business processes to make it easier for companies to manage inventory. PT. Netciti Persada is a telecommunications and broadband service provider in Indonesia, founded in April 2012, with more than 20 years of experience in the telecommunications industry. They provide FTTH (Fiber to the Home) based telecommunications facilities and Broadband - Community Service Provider networks in various areas such as Alam Sutera, Suvarna Sutera, Jabodetabek, Karawang, Surabaya, Bali and Medan. Using fiber optic technology, Netciti offers Quad Play services: Broadband-based Voice, Video, Data and CCTV with unlimited high quality and speed. Currently the company still manages stock of goods manually, namely recording the flow of incoming and outgoing goods.